THE IMPACT OF FINANCIAL TECHNOLOGIES ON THE BANK’S COMPETITIVENESS - Вовчак , Ольга; Пронько, Віра (Socio-economic relations in the digital society, 2020)
Scientific work is devoted to development of innovations of banks of Ukraine under conditions increased competition in the financial market. The necessity of introduction of new financial technologies inbanking activity in the conditions of digital economy is considered, their advantages and risks, which banks in their use are exposed, are exposed. The influence of financial digital innovations on the competitiveness of a banking institution in the current conditions of development of fintech companies is investigated and the involvement of ukrainian banks in cooperation with them is highlighted. The article considers modern banking products and technologies. Not only resources and technical innovations, but also an intellectual capital,technologies of risk-management and marketing strategy which are directed on preservation and expansion of a client base are referred as factors of competitiveness of banks concerning to the author. The experience of introducing financial innovations by foreign banks, including the new generation digital bank from Mbank of Poland and other countries, is revealed. Attention is drawn to the list of internet banking services offered by the largest banks in Ukraine. The analysis of the main financial technologies implemented by domestic banks is carried out and their influence on their competitiveness is revealed. Analyzed the data on the adoption of financial technologies of Ukraine, moreover, how many banks have been recruited before financial and technological companies. The scientific research presented in article reveals the impact of financial technologies on the development of the banking sector. The conclusion is made about the impact of financial technologies on the banking sector and possible ways of development of the banking sector in the new technological conditions. Taking into account the results of the conducted research, the use of the most acceptable ways of transition to the blockchain system and digital technology BigData is proposed.
Keywords: financial technologies; innovations; bank’s competitiveness; internet banking; fintech companies; blockchain